Long-term neurological outcome of acute encephalitis - Aygün, AD; Kabakus, N; Çelik, I; Turgut, M; Yoldas, T; Gök, Ü; Güler, R (Oxford Univ Press, 2001)
To understand the viral etiology of acute childhood encephalitis in Elazig, Eastern Turkey, 36 children aged between 4 months and 14 years who were treated in a regional medical center between January 1995 and June 1999 were studied. Viral etiology was identified in 16 of 34 (47.1 per cent) cases and the most frequently detected pathogens was! mumps (seven cases, 20.6 per cent). No specific etiology was found in 18 (52.9 per cent) cases. Among the survivors, mental and/or focal neurological deficits persisted in 18 (52.9 per cent). Two children died and 32 survived, of whom 16 were left with no neurological sequel, 10 had persistent neurological sequel, and eight recovered with some degree of handicap. Improvement in the general health and sanitation of the population, and the universal use and development of new vaccination will significantly reduce the incidence of viral encephalitis.
Keywords: Children